Effects of plant architecture and drought stress level on lucerne forage quality. (29th December 2016) - Pecetti, L.; Annicchiarico, P.; Scotti, C.; Paolini, M.; Nanni, V.; Palmonari, A.
Abstract: Breeding for enhanced quality in lucerne ( Medicago sativa ) frequently involves selection for higher leaf‐to‐stem ratio, multifoliolate leaves or short‐internode stems. Three populations selected for such alternative morphologies and a reference cultivar were evaluated for forage yield, leaf‐to‐stem ratio and protein and fibre concentrations in leaves, stems and whole plants. Four managed environments were obtained by combining two stress levels (moderate or nil) with two sowing times. The population selected for high leaf‐to‐stem ratio, as well as the short‐internode population, had highest leaf‐to‐stem ratio (1.27) across six harvests in two non‐stress environments. The latter population had higher stem protein (12.9%) and lower stem neutral‐detergent fibre (NDF) concentration (58.7%) than other populations. The multifoliolate population had intermediate quality, showing low expression of the multifoliolate trait (14.0% across four environments), particularly under stress (10.5%). The autumn‐sown, fully irrigated environment had, on average, highest dry‐matter yield (4.19 t ha −1 ) and lowest leaf‐to‐stem ratio (0.74). Drought‐stressed environments had lower plant NDF (−12.3% on average) and leaf protein (−9.7%), and higher stem protein (+8.6%) than fully irrigated environments. The results suggested that environmental effects might have greater impact on quality than genetic effects, even for a population set including material selected for quality‐driven morphology.